Peran Financial Socialization dalam Memediasi Pengaruh Digital Financial Literacy terhadap Digital Financial Behaviour Generasi Z - Billy Mathew Hadap; Evely Evelyn (KOLONI, 2026)
The development of digital financial services provides Generation Z with greater convenience in conducting financial activities, but it also requires proper financial management capabilities. This study aims to examine the effect of digital financial literacy on digital financial behaviour and the mediating role of financial socialization among Generation Z. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 413 Generation Z respondents who reside in Surabaya, earn their own income, and actively use digital financial services. The sampling technique used was purposive sampling, while the data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that digital financial literacy has a significant effect on digital financial behaviour. Furthermore, financial socialization partially mediates the effect of digital financial literacy on digital financial behaviour. These findings indicate that the ability to understand and use digital financial services, supported by financial learning through parents, peers, and digital media, can encourage Generation Z to develop better, more rational, and responsible digital financial behaviour.